Chinese Cross-Border Acquisition Strategies in Japan – Changing from a Resource-Driven to a Market-Driven Approach - Chen, Fei; Ahmed, Kashif; Bebenroth, Ralf (Organizations and Markets in Emerging Economies, 2020)
The aim of this research is the investigation of strategic behavior of Chinese investors in Japan when making cross-border acquisitions in recent times. While previous literature on acquisitions tended to show that Chinese acquirers were merely resource-driven, i.e. their main purpose was to acquire products, brands, and knowledge to be transferred back to the (Chinese) home market, our study suggests that the behavior of many Chinese firms has changed lately. In a pivotal study with 39 Chinese bidders taking over Japanese targets, we find that their strategy has become increasingly market-driven instead. As far as industry-wise acquisitions are concerned, Chinese firms are taking over Japanese hotels and recreation facilities in recent years for the purpose of providing services to Chinese tourists.
Keywords: Chinese MNEs; cross border acquisition; Japan; market-driven; comparative ownership advantages